Understanding the Blended Learning Experiences of English Language Teachers in a Distance TESL Degree Programme in Malaysia (Sains Humanika, 2013)
In an effort to improve the status and the professional qualification of non-graduate primary school teachers, the Ministry of Education, Malaysia recently mandated a large scale change effort to upgrade non-graduate teachers to become graduate teachers via a a specially designed distant education degree programme, called the Graduate Programme for Teachers (Program Pensiswazahan Guru also known as PPG in Malay language) using a blended format involving part face-to-face (F2F) and distance learning. This paper examines the learning experiences of the first cohort of TESL teachers undergoing the blended learning (BL) courses. Specifically, learning experiences were examined in the form of (1) the in-service teachers’ perception towards the BL approach, and (2) the learning experiences supporting or impeding their learning using the BL approach. To gain an appreciation of the in-service teachers’ experience with the BL system, both qualitative and quantitative techniques were used, namely a survey consisting of open and closed questions, focus groups interviews and reflective journals. Findings revealed the teachers generally have positive perceptions of the blended course design. However, when viewed through the theoretical lens of Activity Theory (AT), data revealed tensions both between and within the components of the activity system in the BL environment. The paper concludes that further fine-tuning needs to be taken to ameliorate the challenges faced, particularly the contradictions and tensions involving issues related to willingness and attitudes towards learning the courses (object/outcome component); Schoology and learning materials (Mediating tools); collaboration (Rules) and opinions related to ‘teacher’s presence’ (Division of Labour).
Keywords: Blended learning; distance learning degree; learning experiences; schoology learning management system; activity theory